2018
DOI: 10.5194/hess-22-1525-2018
|View full text |Cite
|
Sign up to set email alerts
|

Multiple causes of nonstationarity in the Weihe annual low-flow series

Abstract: Abstract. Under the background of global climate change and local anthropogenic activities, multiple driving forces have introduced various nonstationary components into lowflow series. This has led to a high demand on low-flow frequency analysis that considers nonstationary conditions for modeling. In this study, through a nonstationary frequency analysis framework with the generalized linear model (GLM) to consider time-varying distribution parameters, the multiple explanatory variables were incorporated to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…However, there is no such restriction in GAMLSS, allowing time series modeling for observations with any underlying distribution (Rigby & Stasinopoulos, ). Because of its ability to relate time series variables with external covariates, GAMLSS has been employed by many studies for nonstationary modeling and attribution (Jiang et al, ; López & Francés, ; Tan & Gan, ; Villarini, Smith, et al, ; Villarini et al, , ; Xiong et al, ; Zhang et al, , ). GAMLSS has also been used for stochastic simulation of climate variables and in weather generators (Chun et al, ; Serinaldi & Kilsby, , ; Tye et al, ; Verdin et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…However, there is no such restriction in GAMLSS, allowing time series modeling for observations with any underlying distribution (Rigby & Stasinopoulos, ). Because of its ability to relate time series variables with external covariates, GAMLSS has been employed by many studies for nonstationary modeling and attribution (Jiang et al, ; López & Francés, ; Tan & Gan, ; Villarini, Smith, et al, ; Villarini et al, , ; Xiong et al, ; Zhang et al, , ). GAMLSS has also been used for stochastic simulation of climate variables and in weather generators (Chun et al, ; Serinaldi & Kilsby, , ; Tye et al, ; Verdin et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…In the case of GGA distribution, considering that the shape parameter 3  is quite sensitive and difficult to estimate, we assumed it to be constant as other studies did (e.g. : Du et al 2015;López and Francés 2013;Xiong et al 2018;Yan, Xiong, Guo, et al 2017). The Akaike Information Criterion (AIC;…”
Section: Model Selection 215mentioning
confidence: 99%
“…Unfortunately, the paucity of progress in model development is partly due to structural inadequacy. For example, dynamic components in hydrological models are oversimplified due to a poor understanding of their physical mechanisms (Xiong et al, 2019;Deng et al, 2016Deng et al, , 2018Dakhlaoui et al, 2017;Sarhadi et al, 2016;Pathiraja et al, 2016;Ouyang et al, 2016). Previous studies have demonstrated that the assumption of time-invariant parameters is usually inappropriate.…”
Section: Introductionmentioning
confidence: 99%